Cytotoxic Sesterterpenoids from a Sponge Hippospongia sp. - Jui-Hsin Su; Mei-Chin Lu; Yalan Chou; Yuan-Shing Ho; Li-Lian Liu; Yu-Chia Chang; Shang-Wei Tseng (Marine Drugs, 2012)
One new pentacyclic sesterterpene, hippospongide A (1), and one new scalarane sesterterpenoid, hippospongide B (2), along with six previously reported known scalarane–type sesterterpenes (3–8), were isolated from a sponge Hippospongia sp. The structures of these compounds were elucidated on the basis of their spectroscopic data and comparison of the NMR data with those of known analogues. These metabolites are the first pentacyclic sesterterpene and scalarane-type sesterterpenes to be reported from this genus. Compounds 3–5 exhibited significant cytotoxicity against DLD-1, HCT-116, T-47D and K562 cancer cell lines.